Educação a distância como possibilidade de qualificação dos recuperandos do sistema prisional - Santos, Thaís Teixeira (2020)
This research is exploratory and qualitative, aimed to investigate the possible contributions of Distance Education offered within a prison system to overcome the limitations imposed by the deprivation of liberty. Participants are recovering from a Association for Protection and Assistance to the Convicted (APAC) in the interior of Minas Gerais. The APAC model is an attempt to respond the crisis of the Brazilian prison system, with its own methodology, based on dignity and without losing the focus of punishment, has in its goals the formation of the inmate as a possibility of inclusion and distance education as one of the strategies for intellectual and human improvement. To respond to the proposed objective, semi-structured interviews, content analysis and three main categories - perspectives, difficulties and differences - were listed in relation to self-perceived changes after insertion in higher education at a distance. Briefly, we can highlight two striking results: higher education viewed positively as a possibility for future reintegration into society and; technology as a means of communication as a difficulty. The data indicated that the challenge is the autonomous construction of knowledge, since many of them were outside the educational system and have difficulties arising from the mastery of content, the manipulation of technologies and the communication model characteristic of distance learning. However, even with the difficulties noted, formation seems to emerge values such as sharing, self-esteem, belonging, organization and dedication.